Role of microRNAs and DNA Methyltransferases in Transmitting Induced Genomic Instability between Cell Generations - Huumonen, Katriina; Korkalainen, Merja; Viluksela, Matti; Lahtinen, Tapani; Naarala, Jonne; Juutilainen, Jukka (Frontiers in Public Health, 2014)
There is limited understanding of how radiation or chemicals induce genomic instability, and how the instability is epigenetically transmitted to the progeny of exposed cells or organisms. Here we measured the expression of microRNAs (miRNAs) and DNA methyltransferases (DNMTs) in murine embryonal fibroblasts exposed to ionizing radiation or 2,3,7,8 -tetrachlorodibenzo-p-dioxin (TCDD), which were previously shown to induce genomic instability in this cell line. Cadmium was used as a reference agent that does not induce genomic instability in our experimental model. Measurements at 8 and 15 days after exposure did not identify any such persistent changes that could be considered as signals transmitting genomic instability to the progeny of exposed cells. However, measurements at 2 days after exposure revealed findings that may reflect initial stages of genomic instability. Changes that were common to TCDD and two doses of radiation (but not to cadmium) included 5 candidate signature miRNAs and general up-regulation of miRNA expression. Expression of DNMT3a, DNMT3b and DNMT2 were suppressed by cadmium but not by TCDD or radiation, consistently with the hypothesis that sufficient expression of DNMTs is necessary in the initial phase of induced genomic instability.